(untitled) (Research Journal of Padmakanya Multiple Campus, 2024)
Organizational commitment is multi-dimensional construct. It is influenced by personal, organizational, environmental, socio-economic factors. It fact, it is an attitude and behavior of employees at work in an organization. This study has tried to identify the organizational commitment variables and level of organizational commitment of official employees in university. 106 official employees’ opinion has been collected by the help of six point Likert Scale. The statistical tools mean, standard deviation and factor analysis has been applied for analysis purpose. The analysis has shown, the organizational commitment level of employees found at slightly committed, and moderately commitment level. But the standard deviation has shown remarkable deviation in organizational commitment among the employees. The factor analysis has shown coefficient value more than .459, refers all the studied variables should represent the organizational commitment of official employees in University. The study has supported three dimension model of Allen and Meyer model (1990). The study has shown three dimension of organizational commitment. The management of university should apply this finding to enhance the organizational commitment of employees in university.